2022
DOI: 10.48550/arxiv.2202.09053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

QED effects on phase transition and Ruppeiner geometry of Euler-Heisenberg-AdS black holes

Abstract: Taking the quantum electrodynamics (QED) effect into account, we study the black hole phase transition and Ruppeiner geometry for the Euler-Heisenberg anti-de Sitter black hole in the extended phase space. For negative and small positive QED parameter, we observe a small/large black hole phase transition and reentrant phase transition, respectively. While a large positive value of the QED parameter ruins the phase transition. The phase diagrams for each case are explicitly exhibited.Then we construct the Ruppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(61 reference statements)
0
3
1
Order By: Relevance
“…In other cases, however, attractive interaction is always dominant, both in IBH and LBH branches. This result is quite different from the RPT case shown by several other black holes [47,76,77], where there are only attractive or repulsive interaction in black holes.…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…In other cases, however, attractive interaction is always dominant, both in IBH and LBH branches. This result is quite different from the RPT case shown by several other black holes [47,76,77], where there are only attractive or repulsive interaction in black holes.…”
contrasting
confidence: 90%
“…It has been suggested that the interaction type in IBHs (or SBHs) near the first-order phase transition line differs for VdW-like PT and RPT. In the VdW-like case, a transition between attractive and repulsive interactions can be found [37,44,46,49,50], whereas for the RPT case, the dominant interaction is always attractive [47,76] or repulsive [77]. In other words, in the RPT case, the IBHs (or SBHs) behave like bosonic gas or fermionic gas, while in the VdW-like PT case, they behave like a quantum anyon gas.…”
Section: B Reentrant Phase Transition Casementioning
confidence: 97%
“…Magos and Breton generalized the solution to the Euler-Heisenberg theory coupled to gravity that represents a nonlinearly charged static black hole by introducing the cosmological constant, and showed that the consistency between the Smarr formula and the first law of black hole thermodynamics [36]. More recently, a complementary paper [37] appeared. In this work, on the free energy landscape, we study the phase transition in the Euler-Heisenberg-AdS black hole by using the Fokker-Planck equation.…”
Section: Introductionmentioning
confidence: 99%
“…The Lagrangian of the nonlinear electrodynamics was first constructed by Heisenberg and Euler by using the Dirac electronpositron theory, and reconstructed by Schwinger in the frame of quantum electrodynamics [66]. Based on the Lagrangian, some interesting solutions of black hole were gotten and their properties were studied [67][68][69][70][71][72][73][74]. An important feature of the AdS black hole is the existence of the phase transitions and critical phenomenon, where the cosmological constant is regarded as a thermodynamic pressure and its conjugate quantity is a thermodynamic volume.…”
Section: Introductionmentioning
confidence: 99%